CONTENT OF INVESTMENT ATTRACTIVENESS OF A REGION ECONOMY AS AN ECONOMIC CATEGORY - Anna A. Vershinina; Natalia Y. Bambaeva (Статистика и экономика)
The article describes the concept of investment attractiveness. The main approaches to its determination are identified; the features of evaluation of investment attractiveness of a region economy are analysed.